Detection of CD9 and CD81 tetraspanins in bovine and porcine oocytes and embryos - Jankovicova, Jana; Secova, Petra; Manaskova-Postlerova, Pavla; Simonik, Ondrej; Frolikova, Michaela; Chmelikova, Eva; Horovska, Lubica; Michalkova, Katarina; Dvorakova-Hortova, Katerina; Antalikova, Jana (International journal of biological macromolecules, 2019)
Tetraspanins are multifunctional molecules located in specific microdomains on the plasma membrane. Thanks to their ability to form networks with other proteins they can participate in many cellular functions. Tetraspanins are part of the interactive network in gametes; however, their precise role in fertilization is not yet clear. The aim of this study was to compare the localization of CD9 and CD81 tetraspanins during oocyte maturation and early development of the embryos in bovine and porcine model. CD9 was detected on the oocyte plasma membrane and vesicles in the perivitelline space of bovine oocytes and embryos. We suggest that CD9 could be a component involved in transzonal projections. Based on the results of in vitro fertilization assay, CD9 and CD81 seem to be part of a more complex fusion network on the plasma membrane of bovine oocytes. On the other hand, both tetraspanins showed a clustered expression pattern on the plasma membrane and inner margin of zona pellucida (ZP) in porcine oocytes and embryos. We found a new species-specific pattern of CD9 and CD81 distribution in ZP which could reflect their specialized role in processes associated with cell adhesion and intercellular communication upon fertilization.
Keywords: prasata; antigeny CD9; Cattle; Swine; Cleavage Stage, Ovum; Cell Line; protilátky; embryo savčí; Tetraspanin 29; oocyty; Metaphase; skot; Fertilization; myši inbrední BALB C; Embryo, Mammalian; Tetraspanin 28; Fertilization in Vitro; Mice, Inbred BALB C; fertilizace in vitro; stadium rýhování vajíčka; partenogeneze; Antibodies; Animals; antigeny CD81; ženské pohlaví; Pig; zvířata; CD9; buněčné linie; metafáze; CD81; Parthenogenesis; Tetraspanins; Female; Embryos; Oocytes